Healthy societies policy, practice and obstacles - Scambler, Graham (Policy Press, 2024)
Re-examining health, healthcare and societal health using the latest data and research, this book addresses definitions of health, changes in health over time and the contribution of healthcare. It also suggests ways of effectively tackling obstacles to improving health and healthcare in twenty-first century Britain